An upper size of vertical axis wind turbines. (2nd August 2013) - Ottermo, F.; Bernhoff, H.
ABSTRACT The scaling behaviour of a straight‐bladed vertical axis wind turbine is considered. A scaling scheme is described that, in the presence of a wind shear profile, aims at leaving the material stresses of the scaled construction unchanged. On the basis of a recent 200 kW three‐bladed H‐rotor design, a structural upper size of the turbine is proposed, this size being the scale at which the gravitational force starts to become important. As gravity has a much worse scaling behaviour than the aerodynamic and centrifugal forces, the construction work will become increasingly more difficult above this scale. The upper size is estimated to be around 30 MW. Copyright © 2013 John Wiley & Sons, Ltd.